The clinical benefit of imaging in the diagnosis and treatment of giant cell arteritis (Swiss Medical Weekly, 2018)
Historically, giant cell arteritis (GCA) was considered to be synonymous with temporal arteritis. However, the disease spectrum of GCA extends much further, and includes vasculitis of the aorta and its branches with or without involvement of the temporal arteries. Imaging is crucial for the diagnosis and follow-up of GCA patients. Large vessel GCA (LV-GCA) often presents as an inflammatory syndrome and is only detected by imaging modalities such as: colour duplex sonography (CDS), computed tomography (CT) / CT angiography (CTA), magnetic resonance imaging (MRI) or 18F-fluorodeoxyglucose positron emission tomography (FDG-PET) / CT. Deciding which imaging modality to use in different clinical situations remains a matter of debate. CDS and MRI enable assessment of the temporal arteries with a presumably higher sensitivity than histology. In the context of a typical presentation, CDS can replace a biopsy. In about a third of patients, the temporal arteries are not involved, thus PET/CT, MRI, CT, or CDS of larger arteries is needed to diagnose GCA. The sensitivity of all modalities is affected by glucocorticoid therapy. Therefore, without delaying therapy, imaging should be performed within a few days of treatment initiation. The use of PET/CT for the work-up of inflammatory syndromes in the elderly reveals vasculitis in approximately 20% of examined patients and uncover relevant diagnoses in the majority of remaining patients. The aorta should be routinely assessed in all GCA patients at diagnosis and during follow-up. MRA or CTA are best suited to characterise structural damage of larger arteries. The role of imaging in monitoring GCA disease activity still needs to be further defined.